Fostering Creativity through Play in Pre-Primary School Children in Nigeria - Adokiye Adolphus Okujagu; Princewill Okechukwu Ejekwu (International Journal on Integrated Education, 2022)
Acquisition of entrepreneurial skills is an imperative for job creation and employment of labour, and for this to thrive, creativity plays a significant role in this direction. Besides, creativity also engenders remarkable progress and advancement of society as well as technological inventions. It is against this background that this discourse focused on fostering creativity through play among children in pre-primary schools in Nigeria. In this article, creativity, its characteristics and importance were reviewed. The concept of play, types and importance were reiterated and strategies to harness creativity skills through the use of play were brought to the fore. The conditions necessary for development of creative skills were emphasized. The article recommended among others, that creative activities should be encouraged among children in the classroom by teachers not strictly tying activities to time and schedules, and that opportunities should be given to children to be cognitively active than basing all children's learning on a curriculum which is geared towards assessment and examination.